Roadway Safety: Logging Truck-Related Crashes in Florida - Serap Gorucu; Madison Moore; Nikolay Bliznyuk (EDIS)
This report summarizes logging truck-related crashes in Florida. It discusses crash characteristics, vehicles, traffic violations, injuries, key findings, and recommendations for safety. Written by Serap Gorucu, Madison Moore, and Nikolay Bliznyuk, and published by the UF/IFAS Department of Agricultural and Biological Engineering, February 2024.